Caraterização da família de proteínas RHS ("retrotransposon hot spot") em Trypanosoma cruzi - Pereira, Werica Bernardo [UNIFESP] (2017)
RHS proteins ("Retrotransposon Hot Spot") are encoded by a multigenic family found only in species of the genus Trypanosoma. RHS refers to a site for insertion of retrotransposons into the RHS gene generating a pseudogene consisting of one or more retroelements flanked by two separate parts of RHS. There are 752 genes RHS in the T. cruzi genome of which 557 are pseudogenes, suggesting a role for HSR in the genomic architecture of trypanosomes. However, despite its biological relevance, the role of HRS remains largely unknown. The objective of the present work is to study the organization and expression of RHS genes in T. cruzi, in order to understand the evolution and function of this genetic family.